WATER SYSTEM OF THE RIVER IN URBAN AREAS THAT AFFECTED BY THE INFLUENCE OF THE TIDES CASE STUDY: TELUK DALAM RIVER IN BANJARMASIN - Widiastuti, Endah; Noor, M. Azhari; Amalia, Maya (CERUCUK, 2019)
Teluk Dalam River is one of the small rivers lays in Banjarmasin. However, when the tides occur, some places such as houses and roads that located around the riverbanks still run into puddles and water system that still need to regulated again. This final project discusses about the water system in urban area that affected by the tides.The method used is the field research in the form of geometrical data every 50 meters conducted along the river, tidal data for 15 days and speed river data. Geometrical data that used is the geometrical data every 100 meters, then that data were input in Autocad Landekstop 2009 to get cross sections and long sections of the river. The tidal data were analyzed through Admiralty method and Worldtides application that will get the results of tidal harmonic constants such as number of Formzahl, MSL, MHHWS, etc. Then the tidal analysis results with the highest elevation MHHWS to be input on river sectional in Autocad. So, we will get cross and long sections of the river that run into tidal water run off and will get a safe levee elevation plans. Digitization of Teluk Dalam river watershed also conducted to determine the land use in the watershed of the river Teluk Dalam.  The Results of the research showed Teluk Dalam River length is 3.55 km, The number of stations that were flooded due to tidal as many as 3 for admiralty method and 16 for worldtides of the total 35 stations, with the water level varied. And for the water system need to clean up the river, raising the riverbanks, and management of  water buildings in Teluk Dalam River.   .Key Words :     Teluk Dalam River, Water Sytem, Channel Cross Section, Tides, Worldtides